A Descriptive Study to Assess the Self-care Attitude and Practice among Nurses from Selected Hospitals of Pune City - Sharadha Ramesh; Poonam Yadav; Shruti Dhabhade (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: To learn Healthy coping strategy should be a part of self-care development for the nursingstaff and the student nurses. It will encourage health and is also a fundamental value for the scopeand standard of practice. The attitude of all the nursing different some are favorable and some are notfavorable towards the positive attitude for the self-care. Some also denote that the attitude should bepositive or negative. Attitude is one the essential part for nursing education7,5,3. Objectives of the Study:1.To assess the self-care attitude among nurses from selected hospitals of Pune City.2. To assess the self-carepractice among nurses from selected hospitals of Pune City. Methodology: Quantitative research approachwas adopted for this study to accomplish the objectives of the study. Result: The analysis of the studysuggests that nurses have positive attitude about their self-care in regards to spiritual wellness, Mentalwellness, Emotional wellness, Nutritional wellness, Social wellness, Intellectual wellness,Physical wellness.But the practice regarding the self-care is very poor among nurses .which an important point to note andthe researcher suggest that there should be proper awareness and practice regrading self-care among nurses.